A Gothic Analysis of India Stoker's Character Development in Film Stoker (2013) - Yulianus Harefa; Sundari Gita Cahyani; Parlindungan Purba (LingPoet: Journal of Linguistics and Literary Research, 2026)
This study analyzes the character development in the film Stoker. India Stoker was the leading character in the movie 'Stoker (2013)'. This study focuses on two research questions: how Stoker is portrayed in the film and how the transformation of India Stoker develops in the film. In analyzing the data, the portrayal of characters using the theory of nine ways proposed by MJ Murphy and the theory of Character development through the plot using the theory of structuralism by Seymour Chatman was used to identify character development in the film Stoker. This study uses descriptive qualitative methods. This research Data is in the form of dialogue and scenes from the transcript of the film Stoker. The source of data in this study is Stoker's Film. This study showed that India Stoker experienced character development from an innocent, isolated, and quiet character at the beginning of the plot. At the end of the story, the character undergoes transformation and development into a confident, independent, and psychopathic tendencies character. The conclusion of this study is that India Stoker, as the leading character, experiences character development along the plot of the film, but India Stoker's development is a negative character development. India Stoker decided to find her own identity and become a confident, Independent, and psychopath character.